A clinical and molecular genetics study of primary congenital glaucoma in South Korea. Issue 11 (1st September 2012) - Suh, Wool; Kee, Changwon
Abstract : Objectives: To investigate the clinical manifestations associated with the mutation spectrums of the human cytochrome P450 ( CYP1B1 ) and myocilin ( MYOC ) genes in South Korean patients with primary congenital glaucoma (PCG). Methods: Eighty-five unrelated PCG patients and their family members of South Korean origin were screened for mutations in the CYP1B1 and MYOC genes by sequencing with the PCR. We analysed phenotypes related to the presence, number and types of CYP1B1 mutations. In addition, the phenotype associated with the MYOC gene mutations was evaluated. Results: There was no statistically significant difference in clinical studies between PCG patients with CYP1B1 mutations (N=63) and those without mutations (N=22), although the mutation group manifested disease earlier, with greater severity, and frequency in both eyes (p>0.05). However, the response to treatments was statistically different between groups and tended to be poor according to the number of mutant alleles (p=0.000, 0.0017). Patients with MYOC mutations (N=2) showed various phenotypic features. Conclusions: No consistent correlation was observed between the initial clinical manifestations and the CYP1B1 genotype. However, the response to treatment was associated with the CYP1B1 mutant alleles. This is the first report discussing the phenotypes of South Korean PCG patients associated with CYP1B1 mutations.